Dynamic trajectories of the triglyceride-glucose index link to all-cause hospital mortality in patients with hypertension and kidney failure: a multicenter study - Huang, Yanqun; Gan, Xin; Liang, Hui; Tang, Senhu; Chen, Junfan; Shi, Yinglong (Frontiers in Endocrinology, 2026)
BackgroundChronic kidney disease and hypertension form a vicious cardiorenal cycle, exacerbating metabolic dysfunction and mortality. The triglyceride-glucose (TyG) index, a surrogate for insulin resistance, has shown prognostic value in cardiovascular and renal diseases. Previous research analyzed single-timepoint TyG, ignoring longitudinal trajectories during hospitalization. We aimed to investigate TyG trajectories and their association with hospital mortality in patients with hypertension and kidney failure (KF).MethodsPatients diagnosed with hypertension and KF were retrospectively retrieved from MIMIC-IV and a private dataset. Patients were clustered into four TyG trajectory groups using K-means clustering. A novel time-weighted average TyG (WATyG) metric was developed to quantify cumulative metabolic exposure. Logistic regression, restricted cubic spline (RCS) models, and subgroup analyses examined associations between TyG dynamics and mortality.ResultsA total of 2,038 patients from MIMIC-IV and 1,266 from a private dataset were analyzed, with mortality rates of 28.41% and 7.03%, respectively. Four TyG trajectories were identified: rapidly increasing (Cluster 1), rapidly decreasing (Cluster 2), persistent high (Cluster 3), and stable low (Cluster 4). Clusters 1 and 3 had significantly higher mortality rates than Clusters 2 and 4 (all P<0.001). In MIMIC-IV, mortality rates were 38.8%/35.0% for Clusters 1/3 versus 22.6%/22.7% for Clusters 2/4, while the private dataset showed rates of 18.5%/7.6% (Clusters 1/3) versus 5.5%/4.0% (Clusters 2/4). Using Cluster 1 as reference in the adjusted model, Cluster 2 (OR 0.546, P=0.007) and Cluster 4 (OR 0.492, P<0.001) showed lower mortality risks in MIMIC-IV, with consistent trends in the private dataset. WATyG was linearly associated with an increased risk of mortality (OR 1.505, P<0.001 in MIMIC-IV).ConclusionsDynamic TyG trajectories are linked to mortality risk in patients with hypertension and KF. WATyG improves risk stratification via cumulative metabolic exposure. Longitudinal TyG monitoring holds potential value for optimizing clinical decision-making by enabling continuous assessment of metabolic risk.